2017
DOI: 10.1016/j.neulet.2017.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic metabolites are associated with visual plasticity in humans

Abstract: Long-term potentiation (LTP) is a basic cellular mechanism underlying learning and memory. LTP-like plasticity in the visual cortex can be induced by high frequency visual stimulation in rodents and humans. Since glutamate plays a fundamental role in LTP, this study investigated if visual cortical glutamate and glutamine levels, measured by proton magnetic resonance spectroscopy (MRS), relate to visual plasticity in humans. Since plasticity requires a delicate excitation and inhibition balance, GABA was also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 72 publications
(86 reference statements)
4
29
0
Order By: Relevance
“…There is growing evidence that the neurotransmitters gamma-aminobutyric acid (GABA) and glutamate (Glu) are functionally related to standard learning paradigms. For example, GABAergic disinhibition appears to be crucial to learning in the motor cortex ( Floyer-Lea et al, 2006 ; Kolasinski et al, 2019 ; Stagg et al, 2011 ), and there appears to be a positive relationship between resting state Glu, glutamine (Gln), or GABA levels and plasticity in the visual and sensory cortices ( Edden et al, 2009 ; Heba et al, 2016 ; Wijtenburg et al., 2017 ). In the case of perceptual learning, it has been shown that plasticity changes induced by presentation of repetitive stimulation applied to the finger tips is abolished in the presence of lorazepam, a GABA A receptor agonist ( Dinse et al., 2003a ).…”
Section: Introductionsupporting
confidence: 89%
“…There is growing evidence that the neurotransmitters gamma-aminobutyric acid (GABA) and glutamate (Glu) are functionally related to standard learning paradigms. For example, GABAergic disinhibition appears to be crucial to learning in the motor cortex ( Floyer-Lea et al, 2006 ; Kolasinski et al, 2019 ; Stagg et al, 2011 ), and there appears to be a positive relationship between resting state Glu, glutamine (Gln), or GABA levels and plasticity in the visual and sensory cortices ( Edden et al, 2009 ; Heba et al, 2016 ; Wijtenburg et al., 2017 ). In the case of perceptual learning, it has been shown that plasticity changes induced by presentation of repetitive stimulation applied to the finger tips is abolished in the presence of lorazepam, a GABA A receptor agonist ( Dinse et al., 2003a ).…”
Section: Introductionsupporting
confidence: 89%
“…Neural activity in the occipital lobe was also studied in different contexts beyond simple visual perception. Wijtenburg ( 17 ) found a positive correlation between GABA and neural activation difference before and after a high frequency visual stimulus, an effect thought to reflect visual plasticity. In agreement with other studies, when only baseline visual stimulation-related activation was used, a negative correlation was found with GABA levels.…”
Section: Resultsmentioning
confidence: 99%
“…Voxels were placed in the midsagittal slice in the occipital cortex ( Figure 1). Data presented here are part of a study of visual plasticity (data not presented but HC published elsewhere (Wijtenburg et al, 2017)) and memory function, thus the rationale for assessing the occipital cortex. Participants were asked to keep their eyes open and remain awake during the study.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%